2008
DOI: 10.1080/07420520801909320
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Circadian Rhythms in Spousally Bereaved Seniors

Abstract: A laboratory study of sleep and circadian rhythms was undertaken in 28 spousally bereaved seniors (≥60 yrs) at least four months after the loss event. Measures taken included two nights of polysomnography (second night used), ∼36 h of continuous core body temperature monitoring, and four assessments of mood and alertness throughout a day. Preceding the laboratory study, two-week diaries were completed, allowing the assessment of lifestyle regularity using the 17-item Social Rhythm Metric (SRM) and the timing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…CG, like MDD and PTSD, is also associated with sleep disturbances (Germain, Caroff, Buysse & Shear, 2005; Hardison, Neimeyer, & Lichstein, 2005; Monk et al, 2008), several psychometric studies have now shown symptoms of these three conditions constitute distinct clusters (e.g., Boelen & van den Bout, 2005; Golden & Dalgleish, 2010; Prigerson et al, 1996; Prigerson, Frank et al, 1995), and that CG represents a distinct syndrome (Boelen, van den Bout, & de Keijser, 2003; Langner & Maercker, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…CG, like MDD and PTSD, is also associated with sleep disturbances (Germain, Caroff, Buysse & Shear, 2005; Hardison, Neimeyer, & Lichstein, 2005; Monk et al, 2008), several psychometric studies have now shown symptoms of these three conditions constitute distinct clusters (e.g., Boelen & van den Bout, 2005; Golden & Dalgleish, 2010; Prigerson et al, 1996; Prigerson, Frank et al, 1995), and that CG represents a distinct syndrome (Boelen, van den Bout, & de Keijser, 2003; Langner & Maercker, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…An average temperature value was then calculated for each 1-hour bin across the 24-hour period. Several studies have established the validity of monitoring cBT using this method (Byrne & Lim, 2007;McKenzie & Osgood, 2004;Monk et al, 2008;Roach et al, 2010).…”
Section: Assessment Of Core Body Temperaturementioning
confidence: 97%
“…It changes not only in its length, depth, and fragility (Bliwise, 1993; Prinz, 2004), but also in its timing. It is likely that at least some of the sleep disruption experienced by healthy older adults (seniors) is the result of circadian timing issues (Monk, 2005) that are orchestrated principally by the master brain clock, the suprachiasmatic nuclei (Dardente & Cermakian, 2007), although sleep may also be affected by various life events, such as illness or the death of a spouse (Monk et al, 2008). Even in healthy seniors, there are significant age-related circadian phase differences (Czeisler et al, 1992; Monk, 2005).…”
Section: Introductionmentioning
confidence: 99%